Kinetika Perubahan Warna Minuman Teh Hijau Sebagai Pengaruh Intensitas Cahaya dan Penambahan Natrium Askorbat - Permadi, Handika; Feri Kusnandar; Dias Indrasti (Program Studi Teknik Kimia, Universitas Pamulang, 2024)
Displaying ready-to-drink tea beverages in well-lit modern markets accelerates color changes in the product due to oxidation reactions. The addition of antioxidants (sodium ascorbate), combined with light control, potentially inhibits color changes during storage. This study aims to evaluate the kinetics of color changes varying light intensities (500, 1000, and 1500 lux) during a 56-day storage period at 25°C, both with and without the addition of sodium ascorbate (200 ppm) during the extraction process. The stored green tea beverages were analyzed for pH levels, brightness levels (L*), °Hue, and sensory. Storing the beverages in well-lit conditions decreases the pH and reduction in brightness level (L*) and °Hue. The reaction rate of pH, L*, °Hue, and ranking test reduction in green tea beverages without the addition of sodium ascorbate at light intensities of 500, 1000, and 1500 lux is higher compared to treatments with sodium ascorbate addition. Color changes in tea beverages stored different light intensities significant correlation between the L*, °Hue, pH, and perceived color. The longer the product remained in well-lit conditions, the more its brightness diminished, displaying an increasingly yellowish-red hue. The addition of sodium ascorbate effectively inhibited color changes for 7 days of storage. Effectiveness diminished over time, dropping from 197.3 ppm at the start to being undetectable by the end of the storage period. Treatment with sodium ascorbate led to a brighter final color and a less pronounced decrease in pH compared to treatments without sodium ascorbate.